SMART ablation of lymphatic oligometastases in the pelvis and abdomen: Clinical and dosimetry outcomes. (March 2022) - Regnery, Sebastian; Buchele, Carolin; Piskorski, Lars; Weykamp, Fabian; Held, Thomas; Eichkorn, Tanja; Rippke, Carolin; Katharina Renkamp, C.; Klüter, Sebastian; Ristau, Jonas; König, Laila; Koerber, Stefan A.; et al.
Graphical abstract: Highlights: Stereotactic MR-guided online adaptive radiotherapy (SMART) as personalized therapy. SMART of 26 patients with 31 abdominopelvic, oligoprogressive lymphatic metastases. Increased planning target volume (PTV) coverage due to plan adaptation (+7%). Avoidance of overdoses to organs-at-risk (OAR) (19% before, <1% after adaptation). Excellent local control without high-grade toxicity despite frequent previous RT. Abstract: Purpose: To demonstrate dosimetry benefits and report clinical outcomes of stereotactic magnetic resonance (MR)-guided online adaptive radiotherapy (SMART) of abdominopelvic lymphatic oligometastases. Patients & Methods: Prospective registry data of 26 patients with 31 oligoprogressive lymphatic metastases (1–2 lesions) who received SMART between April 2020 and April 2021 was analyzed. Prostate cancer was the most common histology (69%). Most patients (63%) had received previous abdominopelvic radiotherapy (RT). SMART was delivered in 3–7 fractions based on planning target volume (PTV) location and previous dose exposures. For SMART, the baseline plan was recalculated on daily 3D MR-imaging (predicted plan), and plan adaptation was mandatory in case of planning objective violations. Results: Plan adaptation was mostly performed due to violation of planning objectives in the predicted plan (134/140 fractions, 96%) and significantly improved plan dosimetry: (1) PTV coverage was increased (predicted: median 89%, adapted: median 95%, p < 0.001), (2) organs-at-risk (OAR) overdoses were reduced (predicted: 27/140 (19%), adapted: 1/140 (1%), p < 0.001) and (3) PTV overdoses were reduced (predicted: 21/140 (15%), adapted: 1/140 (1%), p < 0.001). After a median follow-up of 9.8 months, one patient had in-field tumor progression and twelve patients had out-field tumor progression (at 6 months: progression-free survival: 63% [46–88%], local control rate: 97% [90–100%]). Treatment was tolerated well and no grade ≥3 toxicity was reported. Conclusion: SMART improves target volume coverage and yields superior OAR protection compared to non-adaptive radiotherapy, thus representing an innovative approach to challenging cases, such as repeated radiotherapy.